Influência do turno de trabalho noturno sobre a pressão arterial e prevalência de hipertensão em equipe de enfermagem de hospital de grande porte - Sfredo, Carla Cristina Farias (2009)
Objective: To evaluate the association between shift work and blood pressure, pre-hypertension and hypertension in nursing personnel of a large general hospital. Methods: In a cross-sectional survey, 493 nurses, nurse technicians and assistants, were selected at random in a large general hospital. Hypertension was diagnosed by the mean of four automatic blood pressure readings>= 140/90 mmHg or use of blood pressure lowering agents, and pre-hypertension by systolic blood pressure>= 120-139 or diastolic blood pressure>= 80-89 mmHg. Risk factors for hypertension were evaluated by a standardized questionnaire and anthropometric measurements. The association between turns of work, defined as day or night, and by the combination of turns, and blood pressure, pre-hypertension and hypertension was explored in bivariate and multivariate analyses, controlling for risk factors for hypertension by covariance analysis and modified regression Poisson. Results: The mean age of the participants was 34.3 ± 9.4 years and 88.2% were women. Night shift workers were older, more frequently married or divorced, and less educated. The prevalence of hypertension in the whole sample was 16%, and 28% had pre-hypertension. Blood pressure (after adjustment for confounding) was not different in day and night shift workers. The prevalence of hypertension and pre-hypertension by shift work (day/night and combination of turns) was not different in the bivariate analysis and after adjustment for confounding (all risk ratios = 1.0). Conclusion: Night shift work is not associated with blood pressure, hypertension and pre-hypertension in nurses and nurses assistants working in a large general hospital.